Probiotics as multifaceted oral vaccines against colon cancer: A review - Singh, Shubhi; Singh, Manisha; Gaur, Smriti (Frontiers in Immunology, 2022)
Probiotics are known as the live microorganisms which upon adequate administration elicit a health beneficial response inside the host. The probiotics are known as immunomodulators and exhibit antitumor properties. Advanced research has explored the potential use of probiotics as the oral vaccines delivery systems without the latent risks of pathogenicity. Probiotics based oral vaccines vectors are known to induce mucosal immunity which prevents the host from several enteric infections. Probiotic bacteria have the ability to produce metabolites in the form of anti-inflammatory cytokines, which play an important role in the prevention of carcinogenesis and activating the phagocytes which eliminates the preliminary stage cancer cells. This review discusses the advantages and disadvantages of using the oral probiotic vaccines vectors as well as the mechanism of action of probiotics in colon cancer therapy. This review also employs the use of ‘PROBIO’ database for selecting certain probiotics with immuno modulatory properties. FurtherBesides this, the use of several probiotic bacteria used as anti- colon cancer adjuvants have also been discussed in detail too. Since, current studies and trials are more focused on using the attenuated pathogens instead of using the probiotics based vectors vaccines; the future studies must involve the advanced research in exploiting the potential of several probiotic strains as adjuvants in cancer therapies.